Water : islam Norms and Sciences - Kamil, Iksan Sahri (Eduprof : Islamic Education Journal, 2019)
Classical Muslim scholars discuss water in an early chapter in their book. This shows how important water is in the attention of Muslims as a basic need that Muslims must know. Water in Islam can be argued in two terms. First, in an ecological perspective, the second is in the perspective of mahdhah rituals. First, the concept of imagining water as the basic condition for life and humans as the caliph of Allah fi al-Ardh. It contains an ecological perspective. And the other is for the ritual conditions in Islamic ethics (ilm al-fiqh). Ilm al-fiqh or Islamic ethics says that water is the basic ingredient for eliminating hadath (the forbidden situation for taking Islamic mahdhah rituals) and cleaning najasat (dirty material in the perspective of sharia). On the other hand, science creates a new way to understand the Koran and al-sunnah as a new interpretation of the Koran, especially in nature and all creation in the universe and ritual activities from the perspective of science. Abstrak Sarjana Muslim klasik membahas air pada bab awal dalam buku mereka. Hal tersebut menunjukkan betapa pentingnya air dalam perhatian umat Islam sebagai kebutuhan pokok yang harus diketahui umat Islam. Air dalam Islam bisa diperdebatkan dalam dua istilah. Pertama, dalam perspektif ekologi, kedua dalam perspektif ritual mahdhah. Yang pertama, konsep membayangkan air sebagai kondisi dasar bagi kehidupan dan manusia sebagai khalifah Allah fi al-Ardh. Ini mengandung perspektif ekologi. Dan satunya lagi untuk kondisi ritual dalam etika Islam (ilm al-fiqh). Ilm al-fiqh atau etika Islam mengatakan bahwa air adalah bahan dasar untuk menghilangkan hadath (situasi terlarang untuk mengambil ritual mahdhah Islam) dan membersihkan najasat (bahan kotor dalam perspektif syariah). Di sisi lain, ilmu pengetahuan membuat cara baru untuk memahami Al-quran dan al-sunnah sebagai tafsir baru Al-quran khususnya di alam dan semua ciptaan di alam semesta dan aktivitas ritual dalam perspektif ilmu.